2017
DOI: 10.4049/jimmunol.1700114
|View full text |Cite
|
Sign up to set email alerts
|

Decidual T Cells Exhibit a Highly Differentiated Phenotype and Demonstrate Potential Fetal Specificity and a Strong Transcriptional Response to IFN

Abstract: Immune tolerance during human pregnancy is maintained by a range of modifications to the local and systemic maternal immune system. Lymphoid infiltration is seen at the implantation site of the fetal-maternal interface, and decidual NK cells have been demonstrated to facilitate extravillous trophoblast invasion into maternal decidua during the first trimester, optimizing hemochorial placentation. However, although there is considerable T cell infiltration of the maternal decidua, the functional properties of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
103
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(119 citation statements)
references
References 72 publications
12
103
2
2
Order By: Relevance
“…However, recent studies show that a majority of decidual T-cells are highly differentiated effector and memory cells (Feyaerts et al, 2017;Lissauer et al, 2017). This means that they are experienced antigen-specific T-cells, that probably have been in contact with fetal antigens (Powell et al, 2017). Decidual Tcells have a unique transcriptional profile with high expression of genes involved in inflammatory interferon signaling (Powell et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies show that a majority of decidual T-cells are highly differentiated effector and memory cells (Feyaerts et al, 2017;Lissauer et al, 2017). This means that they are experienced antigen-specific T-cells, that probably have been in contact with fetal antigens (Powell et al, 2017). Decidual Tcells have a unique transcriptional profile with high expression of genes involved in inflammatory interferon signaling (Powell et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Most research concerning inflammation‐induced preterm labor has therefore focused on the innate limb of immunity . Yet, several studies reported strong evidence that T cells, the primary cellular component of the adaptive immune system, are present at the maternal‐fetal interface . More recently, we provided evidence indicating that T cells are also implicated in the mechanisms that lead to labor at term and spontaneous preterm labor .…”
Section: Introductionmentioning
confidence: 81%
“…It undergoes epigenetic silencing on T cells within decidua of pregnant mice 42 . In contrast, CXCR3 is revealed to express on human decidual CD4 + T cells and CD8 + T cells 37,43 . CXCL10‐CXCR3 axis is an important mediator that enable migration of effector cells into decidual tissues 15,44 .…”
Section: Discussionmentioning
confidence: 99%